Genetic and morphological variability analysis revealed a complex network in South-Eastern Sicilian Helichrysum occurrences. (2nd January 2018) - Puglia, G.; Grimaldi, S.; Pavone, P.; Spampinato, G.
Abstract: The Helichrysum occurrences spread over Hyblaean area (Sicily) are characterized by an unusual richness of morphotype variants which ancestral origin is still unclear. Morphological and genetic variability of seven populations attributable to six taxonomic entities ( Helichrysum archimedeum, H. stoechas subsp. conglobatum, H. stoechas subsp. barrelieri, H. hyblaeum, H. pendulum and H. nebrodense ) was examined, in order to highlight their relationships within the Helichrysum sect. Stoechadina. Morphological analysis showed a clear isolation of populations referred to H. pendulum, H. nebrodense and H. stoechas subsp. conglobatum . Whereas, genetic structure profiling, with 21 ISSRs, displayed a strong genetic relationship within H. stoechas and H. archimedeum accessions, where the latter exhibited evident genetic similarity with H. hyblaeum . Analysis of rbcL cpDNA fragment allowed to identify a shared haplotype between H. stoechas and H. rupestre species, while, through the construction of haplotype network based on trnL - F/rpl32 region, the sampled accessions were properly differentiated as confirmed by the cpDNA consensus network. These results confirmed the high affinity of H. archimedeum with other H. stoechas populations and the closer relationship of H. hyblaeum to H. stoechas respect to H. rupestre .